The Northern Sea Route as a Shipping Lane Expectations and Reality - Pastusiak, Tadeusz (Springer International Publishing : Imprint: Springer, 2016)
This book analyses the current and future viability of the Northern Sea Route as a stable transport route for the international transit traffic between Europe and the Far East. It includes the present conditions, defining and evaluating viability factors for using the Northern Sea Route (NSR). The book makes a projection for NSR in the future, taking into account the climatic change in the Arctic findings presented in the IPCC report. This study, based on the author's PhD thesis, analyses meteorological, hydrologic, bathymetric and other data for the evaluation of the navigation criteria. It is intended for a wide spectrum of readers, from students and scientists of Earth sciences and polar geography, navigation, political science researchers and politicians interested in Arctic affairs.